System for calculating and defining classes in modified Monte Alegre Formula - FMA + Sisclass - Coelho Eugenio, Fernando; Rosa dos Santos, Alexandre; Duguy Pedra, Beatriz; Macedo Pezzopane, José Eduardo; Pereira da Silva, Sally Deborah; Fantinel, Roberta Aparecida (Floresta, 2022)
The objective of this work was to develop a computational system for the calculation, storage, and definition of new classes for the forest fire hazard index classified by the Monte Alegre Altered Formula - FMA+, which aims to store the occurrence of forest fires, allowing the generation of statistics on the hazard index and its occurrence, in addition to generating graphical plots and statistics on the performance of the FMA+, the contingency matrix and the monthly analysis of the hazard classes demanded by Nunes et al. (2006) and Eugenio et al. (2020 a). The Sisclass FMA+ application obtained excellent results in previous tests, achieving an increase of up to 31.30% in the percentage of success of the FMA + index. Sisclass FMA+ is accessible to the scientific community and available free of charge.